SYNTHESIS OF NANOPARTICLE SEMICONDUCTOR CdS IN PHASE TRANSFORMED MICROEMULSION OF WATER/ SDS/ ETANOL/ n-HEXANE SYSTEM - Fitria Rahmawati; Abu Masykur; Heni Worowidiyanti (Indonesian Journal of Chemistry, 2005)
The objective of this research is to study wheather the emulsion system of water/SDS (Sodium Dodecyl Sulphate)/ethanol/n-hexane can be transformed from S1 (hydrocarbon in water) type to S2 (water in hydrocarbon). CdS can be synthesized in the transformed product of microemulsion medium. The emulsion type transformation from S1 to S2 was conducted by adding n-hexane increment of 5 mL as hydrocarbon phase and stirring at 300 rpm for 2 minutes. The inversion point was defined from the measurement of emulsion conductivity and was supported by data of the droplet view under optical microscope. CdS was synthesized from reaction of Cd(NO3)2.4H2O with Na2S in phase transformed microemulsion medium. CdS cluster size was obtained from its UV-Vis spectrum and was characterized using X-ray diffraction to analyse the crystallinity and crystal system, then the influence of the variation of SDS amount to the CdS cluster size and its UV-Vis spectrum was observed.The result of this research shows that the system of n-hexane/SDS/water emulsion can be transformed from S1 to S2 type. The SDS amount in the microemulsion has influence the CdS cluster size. The larger amount of SDS added, the smaller of CdS cluster size was obtained. XRD data indicated that CdS cluster has been obtained with 40.613 % of purity.